Peningkatan Kepuasan dan Kinerja Karyawan melalui Manajemen Perencanaan Karir - Zulfadli Hamzah (COSTING : Journal of Economic, Business and Accounting, 2020)
The success of an organization is inseparable from the increase in human resources. This study aims to analyze the career planning process Baitul Maal waa Tamwil (BMT) and its impact on employee performance and job satisfaction. The study was conducted using a quantitative approach. The study population was all employees while the number of samples in this study were 79 people using total sampling techniques. Hypothesis test used in this study was SEM (Structural Equation Modeling) with the PLS program. The results of this study indicate that there is a direct influence between careers planning on employee performance, there is a direct influence between career planning on employee Job Satisfaction, there is a direct effect between satisfaction on employee performance, there is an indirect effect between career planning on performance through employee job satisfaction. Based on the results of the study, make a clear career plan for their employees so that they are more enthusiastic in working and will create job satisfaction which will ultimately improve their performance. Keywords: Career Planning, Job Satisfaction and Employee Performance.